Hierarchical Nanostructured Electrospun Membrane with Periosteum‐Mimic Microenvironment for Enhanced Bone Regeneration. Issue 21 (5th August 2021) - Liu, Laijun; Shang, Yuna; Li, Chaojing; Jiao, Yongjie; Qiu, Yanchen; Wang, Chengyi; Wu, Yuge; Zhang, Qiuyun; Wang, Fujun; Yang, Zhimou; Wang, Lu
Abstract: An ideal periosteum substitute should be able to mimic the periosteum microenvironment that continuously provides growth factors, recruits osteoblasts, and subsequent extracellular matrix (ECM) mineralization to accelerate bone regeneration. Here, a calcium‐binding peptide‐loaded poly( ε ‐caprolactone) (PCL) electrospun membrane modified by the shish‐kebab structure that can mimic the periosteum microenvironment was developed as a bionic periosteum. The calcium‐binding peptide formed by the negatively charged heptaglutamate domain (E7) in the E7‐BMP‐2 with calcium ion in the tricalcium phosphate sol (TCP sol) through electrostatic chelation not only extended the release cycle of E7‐BMP‐2 but also promoted the biomineralization of the bionic periosteum. Cell experiments showed that the bionic periosteum could significantly improve the osteogenic differentiation of the rat‐bone marrow‐derived mesenchymal stem cells (rBMSCs) through both chemical composition and physical structure. The in vivo evaluation of the bionic periosteum confirmed the inherent osteogenesis of this periosteum microenvironment, which could promote the regeneration of vascularized bone tissue. Therefore, the hierarchical nanostructured electrospun membrane with periosteum‐mimic microenvironment is a promising periosteum substitute for the treatment of bone defects. Abstract : In this study, a hierarchical nanostructured electrospun membrane with a periosteum‐mimic microenvironment is successfully constructed by a two‐step method. As a periosteum substitute, it can continuously provide growth factors, recruit osteoblasts, and subsequently promote extracellular matrix mineralization, and shows great clinical advantage in the treatment of critical‐size bone defects with periosteum damage.